Eksistensi Pesantren Nahdlatul Wathan sebagai Agen Perubahan Sosial Keagamaan di Lombok - Lenny Herlina (MANAZHIM, 2022)
The province of NTB has a beautiful island which in 2017 was named a World Halal Tourism Destination. The island is known as the "island of a thousand mosques" not only because the population is predominantly Muslim, but more than that, the people of this island have high enthusiasm in establishing places of worship in the form of mosques and prayer rooms as well as Islamic educational institutions which we later know as Islamic boarding school. There are recorded more than 300 Islamic boarding schools spread across this small island until 2019. This small island is known as the island of Lombok where the existence of Islamic boarding schools as formal and non-formal educational institutions, with all its distinctive roles in the form of; first, as a center for the transmission of Islamic sciences; second, maintaining the continuity of Islamic tradition; and third, as a center for the reproduction of scholars. All of these distinctive roles are consistently carried out by the boarding school community, namely Tuan Guru and santri, while maintaining their Islamic identity without discarding the local wisdom where the boarding school is located, these distinctive and unique characteristics have widely led boarding school as agents of socio-religious change.